Violencia contra periodistas de medios privados durante conflicto social del ecuador en el 2019 - Espinoza Villa, Dayana Yuletsy (2020)
VIOLENCE AGAINST PERIODISTAS OF PRIVATE MEDIA DURING THE SOCIAL CONFLICT OF THE ECUADOR IN 2019 The following investigation describes the aggressions received during the journalistic coverage of private media, of the social conflict of Ecuador aroused in 2019. The study has an overview of the attacks on this guild, which analyzes the type of aggressions and opinions. Through the reference methodological framework, the opinions described in written media publishers were analyzed, which made it possible to determine how society observes this guild.